Indeks plak dan status kesehatan gingiva pada anak usia 7-12 tahun di sekolah dasar negeri 2 dauh puri denpasar - Putu Imas Audina; Putu Ika Anggaraeni; I Made Ady Wirawan (School of Dentistry Faculty of Medicine Udayana University, 2021)
Introduction: Gingivitis is one of the periodontal diseases, a condition where a gingival inflammatory. Gingivitis is generally caused by plaque on the surface of the tooth. Excessive plaque accumulation at the gingival margin causes inflammatory symptoms due to the immune response to the activity of microorganisms in dental plaque. Aim: The purprose of this study was to know plaque index and gingival health status in children of age 7 to 12 years old at Sekolah Dasar Negeri 2 Dauh Puri Method: The design used in this study is a cross sectional study by collecting samples of 128 students aged 7 to 12 years old at Sekolah Dasar Negeri 2 Dauh Puri. The students are divided into groups (subpopulations) and the samples are taken from each group randomly. The plaque index is measured by the O'Leary plaque index and the gingival health status is measured by using the Modified Gingival Index. Result: The results show that the children aged 7 to 12 years old in Sekolah Dasar Negeri 2 Dauh Puri mostly have a very good plaque index (48%). The gingival health status possessed by the children aged 7 to 12 years old in Sekolah Dasar Negeri 2 Dauh Puri is mostly categorized healthy (48%). There are several samples that have a very good plaque index yet there are also some that have mild inflammatory criteria for gingival health (47.01%), which might be caused by some factors other than the plaque itself. Conclusion: The conclusion of this study is the sample which has a very good plaque index, means it also has the healthy criteria of gingival health status found in children aged 7 to 12 years old in Sekolah Dasar Negeri 2 Dauh Puri. Latar Belakang: Penyakit periodontal salah satunya yaitu gingivitis merupakan keadaan inflamasi pada gingiva. Gingivitis umumnya disebabkan oleh plak pada permukaan gigi. Akumulasi plak yang berlebih pada margin gingiva menyebabkan terjadinya gejala inflamasi akibat respon imun terhadap aktivitas mikroorganisme dalam plak gigi. Tujuan: Penelitian ini bertujuan untuk mengetahui indeks plak dan status kesehatan gingiva pada anak usia 7-12 tahun di Sekolah Dasar Negeri 2 Dauh Puri Denpasar. Metode: Desain yang digunakan pada penelitian ini merupakan studi cross sectional. Sampel sebanyak 128 siswa usia 7-12 tahun di Sekolah Dasar Negeri 2 Dauh Puri, dibagi dalam kelompok strata (subpopulasi) dan kemudian sampel diambil dari tiap kelompok strata secara acak. Indeks plak diukur dengan indeks plak O’Leary dan status kesehatan gingiva diukur menggunakan Modified Gingival Index. Hasil: Hasil penelitian menunjukan bahwa indeks plak pada anak usia 7-12 tahun di Sekolah Dasar Negeri 2 Dauh Puri sebagian besar memiliki indeks plak sangat baik (48%). Status kesehatan gingiva yang dimiliki oleh anak usia 7-12 tahun di Sekolah Dasar Negeri 2 Dauh Puri yaitu lebih banyak memiliki status kesehatan gingiva kriteria sehat (48%). Terdapat beberapa sampel yang memiliki indeks plak sangat baik namun memiliki status kesehatan gingiva kriteria inflamasi (47,01%), yang mungkin dapat disebabkan oleh faktor lain selain plak. Simpulan: Kesimpulan penelitian ini adalah sampel yang memiliki indeks plak sangat baik, lebih banyak memiliki status kesehatan gingiva kriteria sehat pada anak usia 7-12 tahun di Sekolah Dasar Negeri 2 Dauh Puri.